The Herschel-ATLAS: a sample of 500 μm-selected lensed galaxies over 600 deg2 - Negrello, M.; Amber, S.; Amvrosiadis, A.; Cai, Z.-Y.; Lapi, A.; Gonzalez-Nuevo, J.; De Zotti, G.; Furlanetto, C.; Maddox, S.J.; Allen, M.; Bakx, T.; Bussmann, R.S.; et al. (Oxford University Press, 2016)
We present a sample of 80 candidate strongly lensed galaxies with flux density above 100 mJy at 500 μm extracted from the Herschel Astrophysical Terahertz Large Area Survey, over an area of 600 deg2. Available imaging and spectroscopic data allow us to confirm the strong lensing in 20 cases and to reject it in one case. For other eight objects, the lensing scenario is strongly supported by the presence of two sources along the same line of sight with distinct photometric redshifts. The remaining objects await more follow-up observations to confirm their nature. The lenses and the background sources have median redshifts zL = 0.6 and zS = 2.5, respectively, and are observed out to zL = 1.2 and zS = 4.2. We measure the number counts of candidate lensed galaxies at 500 μm and compare them with theoretical predictions, finding a good agreement for a maximum magnification of the background sources in the range 10–20. These values are consistent with the magnification factors derived from the lens modelling of individual systems. The catalogue presented here provides sub-mm bright targets for follow-up observations aimed at exploiting gravitational lensing, to study with unprecedented details the morphological and dynamical properties of dusty star-forming regions in z ≳ 1.5 galaxies.